Comparative evaluation of cytotoxic, antimicrobial and antioxidant activities of the crude extracts of three Plectranthus species grown in Saudi Arabia - Ramzi A. Mothana; Jamal M. Khaled; Ali A. El-Gamal; Omar M. Noman; Ashok Kumar; Mohamed F. Alajmi; Adnan J. Al-Rehaily; Mansour S. Al-Said (Elsevier, 2019)
Natural products from medicinal plants represent major resource of novel therapeutic substances for combating serious diseases including cancers and microbial infections. The genus Plectranthus (Family: Labiatae) represents a large and widespread group of species with a diversity of traditional uses in treatment of various ailments. Therefore, this research study aimed to evaluate the cytotoxic, antimicrobial and antioxidant activities of three Plectranthus species growing in Saudi Arabia namely P. cylindraceus Hocst. ex Benth., P. asirensis JRI Wood and P. barbatus Andrews. Moreover, this work focused on the isolation of the active constituents responsible for the activities from the most active Plectranthus species.The extracts were tested for their cytotoxic activity against three cancer cell lines (Hela, HepG2 and HT-29), using MTT-test, antimicrobial activity against Gram positive, Gram negative bacterial and fungal strains using broth micro-dilution assay for minimum inhibitory and bactericidal concentrations (MIC and MBC) and antioxidant activity using scavenging activity of DPPH radical and β-carotene-linoleic acid methods. The ethanolic extracts of the Plectranthus species showed remarkable cytotoxic activity against all cancer cell lines with IC50 values ranging between 10.1 ± 0.33 to 102.6 ± 8.66 μg/mL and a great and antimicrobial activity with MIC values between 62.5 and 250 µg/mL. In addition, the three Plectranthus species showed almost moderate antioxidant activity. The most interesting cytotoxic and antimicrobial results were observed with the extract of P. barbatus. Consequently, this extract was partitioned between water and n-hexane, chloroform and n-butanol and tested. The cytotoxic activity resided predominantly in the n-hexane and chloroform fractions. The analysis of the chloroform fraction led to the isolation of four diterpenoid compounds, two of labdane- and two of abietane-type, which were identified as coleonol B, forskolin, sugiol and 5,6-dehydrosugiol. Purification of the n-hexane fraction led to isolation of a major abietane-type diterpene, which was identified as ferruginol. Sugiol, 5,6-dehydrosugiol and ferruginol were isolated for the first time from P. barbatus in this study. The isolated diterpenoids showed variable cytotoxic effects with IC50 values between 15.1 ± 2.03 and 242 ± 13.3 µg/mL, a great antimicrobial activity with MIC values between 15.6 and 129 µg/mL and a total antioxidant activity ranging from 23.1 ± 2.9 to 69.2 ± 3.8%. Keywords: Plectranthus species, Diterpenoids, Cytotoxic, Antimicrobial, Antioxidant